UPAYA PELIBATAN ORANG TUA PADA MASA PANDEMI COVID-19 DI SEKOLAH DASAR LAZUARDI TURSINA BANYUWANGI - Nur Wiarsih; Ana Fitrotun Nisa (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
This research aims to explain efforts to engage parents during the limited face-to-face learning process at Lazuardi Tursina Banyuwangi Elementary School. This study uses qualitative descriptive methods. The study subjects were teachers and parents at Lazuardi Tursina Banyuwangi Elementary School. The teachers involved in this study as many as 5 people consisted of 3 low-grade teachers and 2 high-class teachers. The parents involved in the study numbered 50 people, consisting of 30 parents of low-grade students and 20 parents of high-class students. The technique of data collection is carried out through interviews, observations, and documentation. The results showed that 85% of parents attended parent meetings, 90% of parents attended parent consultation sessions, 35% of parents were involved in parent teaching sessions, and 85% of parents took advantage of parent guidlines prepared by teachers in accompanying students to learn from home.